Risk analysis of social forestry business management of national economic recovery program in the peatland of Central Kalimantan, Indonesia - Dadang Kusbiantoro; Purwaningsih S. Legowo; Ketut Silvanita; Hasnawir; Irsan Nuryanto (Foresty Faculty of Hasanuddin University, 2022)
Indonesia is one of the countries in the world that has experienced a negative economic impact due to the Covid-19 pandemic since early 2020. In overcoming this impact, the government has taken strategic steps by implementing the National Economic Recovery (PEN) program. One of the PEN programs implemented by the Ministry of Environment and Forestry is community economic development for peat farmer groups through the development of agroforestry food in 35 Social Forestry Business Groups (KUPS) in Pulang Pisau Regency, Central Kalimantan Province. It is one of the regencies known to have quite a large peatland area in Indonesia. This study aimed to analyze the risk management of the 35 KUPS PEN program in peatland. A qualitative desk study methodology was used along with the fishbone model analysis. The results showed that various types of business activities had been developed by KUPS. In the management of social forestry businesses, various riskswere identified starting from regional governance, institutional governance,and business governance. The PEN program implemented in 2020 showed a positive impact in improving the community's economy with a positive impact on ecology and socio-culture. This PEN activity has absorbed around 9,110 HOK (Working People'sDay) local workers with 565 KUPS members. The implementation of this program can be replicated, especially forsocial forestry business groups in other areas.